Gaya dan Model Kepemimpinan Pesantren dalam Meningkatkan Kualitas Santri: Gaya dan Model Kepemimpinan Pesantren dalam Meningkatkan Kualitas Santri - Muzaki , Agifa Rifqi; Wulandari, Novi Diah; Nurcahyanti , Febriani Wahyusari; Idries, Fahmy Akbar (Journal Financial, Business and Economics, 2024)
This research explores the role of leadership in enhancing the quality of students at Bumi Cendekia Islamic Boarding School in Yogyakarta. Leadership in the context of Islamic boarding schools involves nurturing, mentoring, and managing the overall affairs of the institution. The leadership style implemented by the chairman of the foundation of Bumi Cendekia Islamic Boarding School is democratic, allowing active participation of members in decision-making processes. The study employs a qualitative approach using interview, observation, and documentation techniques. Data is analyzed through reduction, presentation, and drawing conclusions. The findings indicate that the foundation's chairman plays a crucial role in shaping the character of students by integrating religious and general education. The applied independent curriculum focuses on the development of morals, knowledge, and skills. The foundation leader assumes a dual role as a manager and a leader, with responsibilities encompassing mentoring, motivation, performance evaluation, and resource management. Democratic leadership creates an inclusive environment where every member feels valued and engaged in the learning process. This research contributes to understanding the role of Islamic boarding school foundation leaders in optimizing student quality. The conclusion emphasizes that effective leadership plays a crucial role in shaping character and advancing the institution, with a democratic style supporting individual growth and development.